2003
DOI: 10.1074/jbc.m301100200
|View full text |Cite
|
Sign up to set email alerts
|

The Human Organic Anion Transport Protein SLC21A6 Is Not Sufficient for Bilirubin Transport

Abstract: Bilirubin is a yellow pigment derived from the degradation of heme. Because of intramolecular hydrogen bonding, it is water insoluble (1). Following formation in various cells throughout the body, it is released into the circulation where it binds avidly to albumin (2, 3). Under normal circumstances, it is extracted from albumin and taken up rapidly by hepatocytes (4, 5). Although the kinetics of uptake suggests carrier mediation, the nature of this carrier has remained elusive (6, 7). The fact that bilirubin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 26 publications
3
49
0
Order By: Relevance
“…In this study, the prevalence of variant 388 in the OATP 2 gene in the case and control groups was 37.5 and 22%, respectively, the former higher than the latter, and the OR for severe hyperbilirubinemia of this variation in the case group was statistically significant. Although it has been reported that OATP 2 is involved in the transportation of both conjugated and unconjugated bilirubins (1), the results of a more recent study showed that a role for OATP 2 in hepatocyte bilirubin transport is unlikely (36). However, the results of this study show that the change of amino acid (aspartic acid to asparagine, encoded by nucleotides 388 -390) at codon 130 of OATP 2 may reduce the function in unconjugated bilirubin elimination, and the mechanism is worthy of further investigation.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, the prevalence of variant 388 in the OATP 2 gene in the case and control groups was 37.5 and 22%, respectively, the former higher than the latter, and the OR for severe hyperbilirubinemia of this variation in the case group was statistically significant. Although it has been reported that OATP 2 is involved in the transportation of both conjugated and unconjugated bilirubins (1), the results of a more recent study showed that a role for OATP 2 in hepatocyte bilirubin transport is unlikely (36). However, the results of this study show that the change of amino acid (aspartic acid to asparagine, encoded by nucleotides 388 -390) at codon 130 of OATP 2 may reduce the function in unconjugated bilirubin elimination, and the mechanism is worthy of further investigation.…”
Section: Discussionmentioning
confidence: 96%
“…Kang et al (26) did not observe any association of these same polymorphisms with bilirubin levels in a Korean sample. For instance, although Cui et al inferred that SLCO1B1 could be the hepatic transporter for bilirubin (7), Wang et al (27) concluded the unlikelihood of this function, and Zucker et al (28) suggested that bilirubin uptake could occur through passive diffusion. Watchko et al (3) reported that G6PD-deficient infants who were homozygous for the G allele of rs2306283 were more common in the icteric group as compared with controls (87.5% vs. 20%, P = 0.015), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A member of the organic anion transporter protein family, termed OATP2/8/C, has been suggested to mediate BR uptake, but it still remains questionable and requires confirmation (Briz et al, 2003;Wang et al, 2003b;Steeg et al, 2010;de Graaf et al, 2011). After entering the hepatocytes, BR binds to glutathione-S-transferases (GSTs), a major group of detoxification enzymes (Levi et al, 1969;Pickett, 1989;Strange et al, 2001).…”
Section: Bilirubin Metabolismmentioning
confidence: 99%